Tratamento descritivo e temático da informação: recomendações para estudos sobre aspectos semióticos na criação de registros bibliográficos - Reis, Daniela Majorie Akama dos (2018)
The creation of bibliographic records is a fundamental process in libraries. Information professionals provide access to documents of a collection through bibliographic records in a catalog. Domain analysis and semiotic aspects are important aspects to consider during documentary reading. This research presents different paths for the study of form and subject cataloging under a semiotic point of view. Form and subject cataloging require contact with the document, which involves complex interpretative processes from the professionals. Two researches on cataloging with different theoretical approaches on semiotics are presented here. The models illustrate the relationship between the document`s subject and its treatment. When the aspects presented in this theoretical study are considered, it is possible to categorize how the professional behaves in contact with the documents.